Efficacy of esomeprazole in treating acid-related diseases in Japanese populations - Furuta T; Sugimoto M (Clinical and Experimental Gastroenterology, 2012)
Mitsushige Sugimoto1, Takahisa Furuta21First Department of Medicine, 2Center for Clinical Research, Hamamatsu University School of Medicine, Shizuoka, JapanAbstract: Esomeprazole (Nexium®; AstraZeneca), the S-isomer of omeprazole, is the first proton pump inhibitor (PPI) to be developed as an optical isomer. Compared with omeprazole, esomeprazole has an improved pharmacokinetic profile with regards to CYP2C19 (S-mephenytoin 4'-hydroxylase) genotype, showing increased systemic exposure and less interindividual variability. Further, esomeprazole is a more potent acid inhibitor than other currently available PPIs and is therefore used as a first-line drug for acid-related diseases. While esomeprazole has been available in a number of countries worldwide, the compound only received authorized permission to be marketed in Japan in September 2011. The standard esomeprazole dose in Japan for the treatment of peptic ulcers and gastroesophageal reflux disease (GERD) is 20 mg. Other advised dosages are 10 mg for nonerosive reflux disease and 20 mg twice-daily dosing for eradication of Helicobacter pylori. In Japanese, the effective rate of esomeprazole 20 mg during 24 weeks for GERD patients is 92.0% (88.0%–96.0%), while the prevention of peptic ulcer development using 20 mg for 24 weeks in patients treated with nonsteroidal anti-inflammatory drugs is 96.0% (92.8%–99.1%). Although clinical data are limited, the usefulness of esomeprazole is expected in Japanese subjects given the reduced prevalence of CYP2C19 rapid metabolizers in Japan compared with Western countries.Keywords: esomeprazole, PPI, CYP2C19, peptic ulcer, GERD, H. pylori